Reducing complexity and compliance costs: a simplification safe harbour for the global minimum tax - Deborah Schanz (Fiscal Studies, 2023)
I present a simplification safe harbour based on tax administrative guidance for Pillar Two, the global minimum tax, developed together with Cedric Döllefeld, Joachim Englisch, Simon Harst and Felix Siegel. It aims at reducing unnecessary compliance costs by avoiding effective tax rate (ETR) calculations if a minimum tax of 15 per cent has already been paid. The simplification safe harbour consists of a two-level test to determine if a full GloBE ETR calculation is required from a multinational enterprise (MNE) or if a simplified ETR calculation or no calculation at all is sufficient. The test consists of a country-level test and – only if necessary – an MNE-level test. The country-level test assesses a country's tax system. It seeks to determine whether the national tax system's nominal tax rates are (too) low and whether significant deviations between a country's tax base and the GloBE income exist. The second level, the MNE-level test, is only carried out if the country-level test has identified potential `red flags'. Even if this second test is required, the simplification safe harbour offers a significant reduction in compliance costs. This reduction is achieved by relying on national tax data, which are readily available in firms, instead of highly adjusted accounting data.
Keywords: 330; BEPS; effective tax rate; GloBE; global minimum tax; Pillar Two; simplification; safe harbour